GROUP DISCUSSION AND LETTER-WRITING EXERCISE - BOGDAN, ROBERT (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Description of three hypothetical situations written through letters related to people with disabilities for class discussion.